2022
DOI: 10.1155/2022/2877728
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential miRNA-mRNA Regulatory Network Contributing to Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disease, and the mechanism underlying PD pathogenesis is not completely understood. Increasing evidence indicates that microRNAs (miRNAs) play a critical regulatory role in the pathogenesis of PD. This study aimed to explore the miRNA-mRNA regulatory network for PD. The differentially expressed miRNAs (DEmis) and genes (DEGs) between PD patients and healthy donors were screened from the miRNA dataset GSE16658 and mRNA dataset GSE100054 downloaded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…MiRNAs can cross the blood-brain barrier and enter body fluids as blood, urine and saliva. In addition, miRNAs are stable, easily quantifiable and accessible by minimally-invasive procedures [6] Several studies have shown that specific panels of miRNAs are dysregulated in PD and other parkinsonian disorders [7,8]. Such evidence shows that the use of miRNAs as biomarkers has great potential for early PD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs can cross the blood-brain barrier and enter body fluids as blood, urine and saliva. In addition, miRNAs are stable, easily quantifiable and accessible by minimally-invasive procedures [6] Several studies have shown that specific panels of miRNAs are dysregulated in PD and other parkinsonian disorders [7,8]. Such evidence shows that the use of miRNAs as biomarkers has great potential for early PD diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, miR-30b-5p levels in serum exosomes helped to distinguish relapsing-remitting from progressive MS ( 43 ). Finally, the levels of miR-30e-5p were downregulated in the blood of patients with Parkinson disease compared with controls ( 44 ), but no reports on the role of miR-30e-5p have been found in MS.…”
Section: Discussionmentioning
confidence: 99%
“…As leptin and BDNF activate shared signaling pathways, such as PI3K and MAPK/ERK and some intermediary molecules, including SH2 and GRB2, leptin could induce positive feedback by increasing BDNF expression. In a recent report [ 126 ], 10 PD-related hub genes, including JAK2, ObRb and IRS2, among others, are involved in AMPK and leptin signaling.…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%